DETERMINANTS OF PREDIABETES AMONG ADULTS IN EAST JAVA: A SECONDARY ANALYSIS OF THE 2023 NATIONAL INDONESIAN HEALTH SURVEY - Roma Yuliana; Putri Rahmadani; Prasita Ayu Widyaningtyas; Ahmad Fauzi; Artha Budi Susila Duarsa; Ikrimah Nafilata; Yuli Puspita Devi; Yasmin Harun (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Prediabetes is an intermediate state between normoglycemia and diabetes mellitus (DM) that may progress to type 2 DM and increase the risk of cardiometabolic complications. Data from the 2023 Indonesian Health Survey reported a prediabetes prevalence of 39.2% among Indonesian adults, indicating a substantial public health burden that requires serious attention. This study aimed to identify the determinants of prediabetes among adults in East Java Province. A cross-sectional study was conducted using secondary data from the 2023 SKI. The study sample consisted of 1,518 adults in East Java Province with complete HbA1c examination data. The results showed that the proportion of prediabetes was 56.0%. In the final multivariable model, factors associated with prediabetes were age ≥35 years (aOR = 1.32; 95% CI: 1.01–1.73), male sex (aOR = 3.24; 95% CI: 2.30–4.57), living in rural areas (aOR = 1.45; 95% CI: 1.01–2.09), hypertension (aOR = 1.43; 95% CI: 1.08–1.90), and dyslipidemia (aOR = 2.23; 95% CI: 1.15–4.34). Age, sex, residential area, hypertension, and dyslipidemia were determinants of prediabetes among adults in East Java. Early screening and lifestyle interventions should be prioritized for high-risk groups.